Co, Fe codoped holey carbon nanosheets as bifunctional oxygen electrocatalysts for rechargeable Zn-air batteries - Zhang, Xueting; Zhu, Zhenye; Tan, Yuanbo; Qin, Ke; Ma, Fei-Xiang; Zhang, Jiaheng (Chemical communications (Cambridge, England), 2021)
Unique Co, Fe codoped holey carbon nanosheets with high surface area and abundant bimetal single atoms (CoFe@HNSs) exhibited remarkable bifunctional oxygen electrocatalytic activity (0.704 V) with very positive half-wave potential (0.897 V) for the ORR and small potential (1.601 V) to drive 10 mA cm −2 for the OER, outperforming commercial Pt/C and IrO 2 , respectively. Furthermore, as the air-cathode for rechargeable Zn-air batteries, the CoFe@HNS based device exhibits a high-power density of 131.3 mW cm −2 and long-term stability over 140 h, indicating the attractive potential of CoFe@HNSs applied in energy storage and conversion. CoFe@HNSs exhibited bifunctional oxygen electrocatalytic activity, and exhibit a high-power density of 131.3 mW cm −2 and long-term stability over 140 h.